В решении.
Объяснение:
1.
а) 9a² – 12ab + 4b² = квадрат разности =
= (3a - 2b)²;
б) (3a – 2b)² = квадрат разности=
= 9a² - 12ab + 4b²;
в) 9a² – 4b² = разность квадратов=
= (3a - 2b)*(3a + 2b);
г) (3a + 2b)² = квадрат суммы =
= 9a² + 12ab + 4b²;
Разложите на множители:
16k² – 49п² = разность квадратов=
= (4k - 7n)*(4k + 7n);
2.
а) (4k – 7n)² = квадрат разности=
= 16k² - 56kn + 49n²;
б) (16k – 49n)² = квадрат разности=
= 256k² - 1568kn + 2401n²;
в) (4k – 7n)(4k + 7n) = разность квадратов=
=16k² - 49n²;
г) (4k + 7n)² = квадрат суммы=
= 16k² + 56kn + 49n².
(x-1)^2+(x+1)^2=(x+2)^2-2x+2
x^2-2x+1+x^2+2x+1=x^2+4x+4-2x+2
2x^2+2=x^2+2x+6
2x^2+2-x^2-2x-6=0
x^2-2x-4=0
D=4+16=20>0
x=1-√5
x=1+√5
ОТВЕТ: 1±√5